Translator’s Tendency in Translating Indonesian Cultural Words into English from The Novel Negeri 5 Menara (The Land of Five Towers) - Intan Kartika Sari (Universitas Pendidikan Indonesia (UPI), 2014)
This research analyzes narrative techniques in Sue Monk Kidd’s novel The Secret Life of Bees (2002) by using Barry’s version (2002) of Genette’s Narratology theory (1980). The purpose of the research is to identify how the story is narrated and how the narrative constructs the main character as evidenced in the novel. By applying the theory, this research attempts to gain insights into how the narrative is presented to the reader in the form of first person mode. This research employs a descriptive qualitative method. This research finds that the story The Secret Life of Bees is narrated through six narrative categorizations: narrative level, narrative time, narrative voice, focalization, narrative of words, and narrative mode. Moreover, the narrative constructs the main character through four methods of characterizations: physical description, dialogue and actions, thoughts and feelings, and what other characters’ say about the main character. This research implies that the story The Secret Life of Bees is well organized. The use of first person narrative and the presence of child character who is also the narrator have made the story interesting and easy to follow. Furthermore, the development of the main character also plays a crucial role in giving the clue to the story’s meaning and successfully covers the major theme of the story.Keywords: Cultural Words, Translator’s Tendency